Management of Seminal Vesicular Tumors in Port Harcourt, Southern Nigeria - Ofuru, Vitalis Obisike; Abhulimen , Abhulimen Victor (International Journal of Health Sciences, 2022)
Tumours of the seminal vesicle are rare. Because of the location of the organ, the clinical manifestation is indistinct and diagnosis is difficult. The purpose of the study is to discuss the management of adenocarcinoma of the seminal vesicle using two consecutive patients with seminal vesicle tumours who presented late with features suggestive of typical prostate neoplasm and were misdiagnosed even after contrast enhanced Computerized Tomography scan as case studies. To highlight the challenges encountered in diagnosis of seminal vesicle tumour and to review the literature on the management of the disease.